PENGARUH KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN DI RUANG HEMODIALISA RSUD MERAUKE - Suriyani, Suriyani (NHM PRESS, 2022)
Patients with kidney failure will be treated in the Hemodialysis room where good therapeutic communication is needed from the nurses. The purpose of this study was to determine the effect of therapeutic communication on patient satisfaction in the Hemodialysis Room at Merauke Hospital. The research design is a quantitative study with a cross-sectional design. The population in this study were all nurses on duty in the Hemodialysis treatment room and all routine patients undergoing Hemodialysis who were willing to be respondents. The sampling technique is total sampling. The number of samples is 51 respondents. The research plan was carried out in the Hemodialysis room at the Merauke Regional General Hospital. During October to November 2020. Bivariate analysis tests were made with Kendall's Tau. The results of the study obtained a value of 0.000 (<0.05) so that the conclusion was that there was an effect of therapeutic communication on patient satisfaction in the Hemodialysis Room at Merauke Hospital. Suggestion: Suggestions for the Merauke Hospital to continue to conduct training on therapeutic communication so that therapeutic communication continues to be improved so as to increase patient satisfaction at Merauke Hospital.